Some New Lacunary Strong Convergent Vector-Valued Sequence Spaces - M. Mursaleen; A. Alotaibi; Sunil K. Sharma (Abstract and Applied Analysis)
We introduce some vector-valued sequence spaces defined by a Musielak-Orlicz function and the concepts of lacunary convergence and strong (A)-convergence, where A=(aik) is an infinite matrix of complex numbers. We also make an effort to study some topological properties and some inclusion relations between these spaces.